Evaluación de la eficiencia y costos de la barita importada de Perú respecto a la nacional como densificante en la perforación de un bloque en Campo Castilla (2019)
Nowadays in Colombia the barite’s extraction is made by a few companies, which use intermediaries to deliver the product to the companies that require it. Once the mineral is extracted, they have to send it to a pounding process and a refinement process to be packed on lumps, which are packed in sacks, a plastic covers and stowage. To their storage it is needed a wide accommodation on the field, where you can find a backup of barite and the needed to add at the mud of the well. When you are going to add the barite, it is used to be in a rustic way, where the workers have to used their own strength to add the bags on the drilling mud.